AKTIVASI ARANG TEMPURUNG KELAPA DENGAN ZNCL2 DAN APLIKASINYA DALAM PENGOLAHAN MINYAK JELANTAH - Pakiding, Lewi Michal; Sumarni, Ni Ketut; Musafira, Musafira (Univ. Tadulako, 2014)
Coconut shell charcoal as an agricultural waste material is high enough containing carbon. This underlying that coconut shell charcoal can be used as raw material of activated charcoal in purification of used cooking oil. Activator of the charcoal was 45% ZnCl2 in various time of heating at 110oC oven , i.e. 2 hours, 2.5 hours, 3 hours; 3.5 hours and 4 hours, then it was followed by various contact time in purification of used cooking oil, that were 1 hour, 2 hours , 3 hours, 4 hours and 5 hours. The obtained results showed that the best time to be used warming was 3.5 hours, which the iodine absorption was 626.25 mg/g. While the optimum contact time for adsorption was 2 hours. Clarity test was done based on several parameters, namely thiobarbiturat (TBA) value, peroxide value and free fatty acid (FFA) content. The results were 0.471042 mg/kg of malonaldehida, 9.1 meq/kg and 0.17152 % FFA respectively. Furthermore, colour test was done by using spectrophotometer, it was obtained the T value of 1.62%.